Tests of Ash Content, Moisture Content and Dry Shrinkage of Ethanol Extracts of Capidada Leaves (Sonneratia alba) and Ketapang (Terminilia cattapa) - Annisa Meyndra Komala; Haryoto Haryoto (Journal of Nutraceuticals and Herbal Medicine, 2020)
Indonesian original medicine requires new development, one of the important stages is by testing which can be used as a parameter to determine standards for certain extracts. Capidada leaves (Sonneratia alba J. Smith) and ketapang leaves (Terminalia cattapa L.) are a type of mangrove that have various activities such as anti-bacterial, anti-inflammatory, antioxidant, as well as the benefits of capidada leaves and ketapang leaves. Therefore, it is necessary to standardize extracts to ensure quality that matches the quality. This research tries to test the water content, ash content, and drying shrinkage levels, which later can be used as a reference for the determination of extract quality standards. The extract was obtained through maceration using 96% ethanol. Test results obtained on capidada leaves are water content (10,38 ±0,52%v/b), total ash content (17,97±1,75%), drying shrinkage levels (10,35±0,35%), and the test results obtained for the ketapang leaves are water content (7,08±0,38%), total ash content (10,51±0,43%) and drying shrinkage levels (13,67±1,58%). To find out all aspects that are not directly related to pharmacological activities but affect the aspects of quality, safety, the stability of extracts and preparations produced, this research studied the ash content, water content, and drying shrinkage levels on ethanol extracts of mangrove capidada leaves (Sonneratia alba) J. Smith.) And ketapang (Terminalia cattapa L.)